The Role of Consumer Trust in Linking Product Quality, Price, and Promotion to Fast Food Purchase Decisions - Sulistiyo, Ajik; Simanjuntak, Vera Clara (LifeSciFi, 2025)
This study aims to examine the mediating role of consumer trust in the relationship between product quality, price, and promotion (exogenous variables) and purchasing decisions (endogenous variable) in the ready-to-eat food sector. As competition intensifies in this industry, identifying the factors that influence consumer behavior becomes increasingly important. Employing a qualitative approach with an exploratory study design, data were collected through in-depth interviews and focus group discussions involving purposively selected consumers who regularly purchased ready-to-eat meals in the past three months. Thematic analysis was used to interpret the data and identify key patterns. The findings reveal that while product quality, competitive pricing, and relevant promotions contribute to shaping purchasing behavior, these factors are insufficient without the presence of strong consumer trust. Trust acts as a crucial psychological bridge that links marketing strategies to consumer action. When trust is established, perceived risk decreases, and consumers are more likely to follow through with a purchase. These insights emphasize the importance of trust-building in marketing strategies, suggesting that businesses in the ready-to-eat food industry should not only focus on product attributes but also invest in fostering long-term consumer confidence to drive sustainable purchasing behavior.